Clinicopathological Analysis of Eyelid Masses: A Cross-sectional Study - Kharel, Ramita; Bhattarai, Binita; Manandhar, Laxmi Devi; Dhakal, Sabita; Adhikari, Jeevan (Journal of Nepalgunj Medical College, 2025)
Introduction: Eye lid masses are common presentations in ophthalmic practices, ranging from benign lesions to potentially life-threatening malignancies. While the clinical examination provides the initial diagnosis, histopathological evaluation remains the gold standard for accurate identification and management. Limited studies in Nepal have explored the clinicopathological correlation of eyelid tumors.Aims: To analyze the demographic profile, clinical presentation, and histopathological findings of benign and malignant eyelid masses, and to assess the correlation between clinical and histopathological diagnosis.Methods: This hospital based cross sectional study was conducted from May 2022 to May 2023 in the department of oculoplasty, Lumbini eye institute and research Centre. Total 53 patients presenting with eye lid masses underwent detailed ocular examination, surgical excision and histopathological analysis. Data were analyzed using SPSS version 22.0.Results: Among 53 patients, 30(56%) were female and 23(43%) male in both benign and malignant eyelid masses. Left upper lid was predominantly affected. The predominant clinical presentation was eye lid mass 33(62.26%) followed by pigmentary changes 8(15.09%). Ulcerated wounds and mechanical ptosis were equally observed in about 5(9.4%) cases each, while mechanical ectropion was the least common presentation, seen in 2(3.7%) cases. Histopathological analysis revealed 44(83%) as benign lesion and 9(17%) as malignant. The most common type of benign lesion was cyst (epidermal, inclusion, and sebaceous types) accounting for 19(43.8%) cases, followed by Nevi (simple, compound and intradermal) and papilloma ecompromising 8(18.8%)cases each. Among malignancies, Basal cell carcinoma 4 (44.44%) was most common followed by sebaceous cell carcinoma 3(33.33%). The overall clinical diagnostic accuracy compared to histopathological diagnosis was 75%.Conclusion: Benign eyelid lesions were more prevalent than malignant ones, with cysts being the most common benign lesion and basal cell carcinoma the most frequent malignancy. Only clinical examination may not be sufficient for accurate diagnosis; therefore, histopathological evaluation is essential for guiding appropriate management.